Budget impact of rosuvastatin initiation in high-risk hyperlipidemic patients from a US managed care perspective. (July 2013) - Montouchet, C.; Ruff, L.; Balu, S.
Abstract Introduction: Statins reduce low-density lipoprotein cholesterol (LDL-C) levels, which, when elevated, represent a significant risk factor for cardiovascular (CV) disease. Hyperlipidemic patients at risk of CV events initiated on simvastatin or atorvastatin may be less likely to meet LDL-C goals (defined in National Cholesterol Education Program guidelines) and more likely to experience CV events than patients initiated on rosuvastatin. A 3-year budget impact model was developed to estimate the clinical impact and cost to a US managed care organization (MCO) with 1 million members of initiating high-risk hyperlipidemic patients on rosuvastatin rather than simvastatin or atorvastatin. Methods: A total of 1000 adult patients were assumed to initiate statins. The average baseline LDL-C level was 189 mg/dL. In scenario 1, all patients were initiated on simvastatin or atorvastatin and titrated to a higher dose, or switched to atorvastatin (if initiated on simvastatin) or rosuvastatin; in scenario 2, 50% of the 520 high-risk patients were initiated on rosuvastatin. Drug acquisition and administration costs were considered. Product labeling, clinical trial results, national prescription claims data, and published literature were used to populate the model. Results: Over 3 years, 75 additional patients reached their LDL-C goal in scenario 2, compared with scenario 1 (633 vs 558, respectively), at an increased cost of $240, 628 ($1, 415, 516 vs $1, 174, 888, respectively). The additional per member per month (PMPM) cost of scenario 2 was $0.007. Limitations: This analysis assumed that statin efficacy is the same in real life as in trials, and used titration and switching patterns not based on patients' goal attainment. However, sensitivity and scenario analyses showed that the model was less sensitive to these parameters than to cost-related parameters. Conclusions: Initiating high-risk hyperlipidemic patients on rosuvastatin may increase the number of patients reaching LDL-C goal at a relatively modest increase in PMPM cost to an MCO.